Aromatic Glycoside from Flue-Cured Tobacco (Nicotiana tabacum) Leaves and its Pyrolysis Behavior Studied by Pyrolysis-GC/MS - Yuan, Y.; Zhou, R.; Li, D.L.; Feng, G.L. (Asian Journal of Chemistry, 2014)
The aromatic glycoside, named benzyl-6-O-a-L-arabinopyranosyl(1-6)-b-D-glucopyranoside, was isolated from the leaves of Nicotiana tabacum L. The structure of which was elucidated by analysis of its spectroscopic data. This compound's thermal behavior and pyrolysis products were also investigated by on-line pyrolysis-gas chromatography mass spectroscopy (Py-GC/MS) at 300, 500, 700, 900 °C. The results indicated that, due to the primary decomposition reaction of the O-glycosidic bound's cleavage, the characteristic and main pyrolysis product was the typical aroma constituent benzyl alcohol, suggesting that glycoside would contribute to produce specific aroma for tobacco products on heating as a novel aroma precursor.